Pendidikan Karakter Anak Usia Dini pada Surah Luqman Ayat 12-19 Berdasarkan Tafsir Ibnu Katsir - Mafaza Amrillah; Ainun Nadlif (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Character education is the most important aspect of a child's life. Character education should be given from an early age so that children develop habits and form good moral character. This research was conducted to find patterns of education for children that are found in Surah Luqman verses 12-19 according to the interpretation of Ibn Kathir. This study used a qualitative approach with a literature study, using documentation techniques and content analysis to obtain valid results. The results of this study are three aspects of moral education for children conducted by Luqman, namely 1) Education of Tawheed (Monotheism), 2) Education of Shariah (Religious Law), and 3) Education of Morality. Suggestions that can be given are further research using the basis of other surahs in the Qur'an and different interpretations.